2021
DOI: 10.3390/diagnostics11081421
|View full text |Cite
|
Sign up to set email alerts
|

Alavi–Carlsen Calcification Score (ACCS): A Simple Measure of Global Cardiac Atherosclerosis Burden

Abstract: Multislice cardiac CT characterizes late stage macrocalcification in epicardial arteries as opposed to PET/CT, which mirrors early phase arterial wall changes in epicardial and transmural coronary arteries. With regard to tracer, there has been a shift from using mainly 18F-fluorodeoxyglucose (FDG), indicating inflammation, to applying predominantly 18F-sodium fluoride (NaF) due to its high affinity for arterial wall microcalcification and more consistent association with cardiovascular risk factors. To make N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…However, assessment of the overall disease burden may provide more valuable information than a lesion-based approach in risk stratification [34]. Additionally, measurements using easily identifiable and well-defined structures allow for easily replicable approaches analysis amenable to analysis by artificial intelligence [35]. Previous studies have demonstrated the superiority of this approach in measuring CVD burden in various disease conditions such as multiple myeloma and type 2 diabetes [36,37].…”
Section: Molecular Imagingmentioning
confidence: 99%
“…However, assessment of the overall disease burden may provide more valuable information than a lesion-based approach in risk stratification [34]. Additionally, measurements using easily identifiable and well-defined structures allow for easily replicable approaches analysis amenable to analysis by artificial intelligence [35]. Previous studies have demonstrated the superiority of this approach in measuring CVD burden in various disease conditions such as multiple myeloma and type 2 diabetes [36,37].…”
Section: Molecular Imagingmentioning
confidence: 99%
“…In the current state of research, the prognostic value and implementation of FDG-PET for the assessment of the atherosclerotic risk remain to be further tested. There has been no clear association between the FDG uptake and CT calcium burden, nor a prospective study in noncancerous patients that correlates an increased FDG uptake with adverse cardiovascular outcomes [91]. The CAMONA (Cardio-vascular Molecular Calcification Assessed by 18 F-NaF PET/CT) study involving 50 patients with angina pectoris and 89 healthy controls, for instance, revealed no significant correlation of FDG uptake in the thoracic aorta and 10-year Framingham Risk Score (FRS) [34].…”
Section: Role Of Fdg In Atherosclerosismentioning
confidence: 99%
“…There currently has not been any human studies establishing a clear link between arterial NaF uptake by macrocalcification and the subsequent transformation into CT-detectable macrocalcification; the clearest association with early NaF uptake and corresponding coronary macrocalcification was demonstrated using an Ossabaw miniature swine model for metabolic syndrome [ 19 ]. Therefore, the development of well-powered, prognostic studies conducted with longitudinal design remains necessary to fill this void and confirm the potential of NaF-PET for the clinical assessment of atherosclerosis [ 91 ].…”
Section: Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…By adopting NaF PET, this limitation is overcome, and the presence of the plaques in the coronaries can be successfully assessed 35,36 . By adopting global disease assessment approach with PET, it is logical to determine the extent of the disease in the entire coronary arteries 37 . This advantage will also have a revolutionary impact on the role of PET in this very important and common disease.…”
mentioning
confidence: 99%